A revision of Attalea (Arecaceae, Arecoideae, Cocoseae, Attaleinae) - Henderson, Andrew (Phytotaxa, 2020)
A taxonomic revision of the neotropical palm genus Attalea based on morphological data was carried out. Nine hundred and two herbarium specimens were scored for 21 quantitative and 33 qualitative variables. Using the Phylogenetic Species Concept, qualitative variables were used to recognize 30 species. These are widely distributed in Central and South America from Mexico to Bolivia and Paraguay, with one species in Haiti. Nomenclature, descriptions, and distribution maps are provided for each species. Qualitative variables are illustrated, and illustrations of 22 living plants are also provided.